(untitled) (Bioagro, 2020)
The identification of agronomical interesting genes is facilitated by the use of molecular markers linked to them that allow the selection of genotypes with the traits of interest. With the aim to identify potato materials (Solanum tuberosum) with late blight (Phytophthora infestans) resistance genes, five combinations of SCAR (sequence characterized amplified region) molecular marker primers were used. Tuber samples were collected from 12 farms of Constanza county, 3 of San José de Ocoa and seven varieties available at commercial stores. From these tubers, 116 in vitro plantlets were established, taking leave samples for DNA isolation. The DNA was amplified by PCR and visualized using electrophoresis on 2% agarose gels. The gels were digitalized and later analyzed by the presence and absence of amplicons, as well as comparing the observed versus the expected size of the bands. Polymorphic and monomorphic fragments were obtained for the total of cultivars in each studied marker; which corresponded to alleles related to the resistance to P. infestans. Marker GP179 yielded a monomorphic fragment of 570 bp. For PrP1 the resulting alleles showed some relationship with the studied varieties. R1, a characteristic fragment of the R1 resistance gene, was found only in the CPC336 (positive check), whereas CosA was present in a Granola variety sample and in CPC336. This is the first report of using this type of markers for detection of disease resistance that is indicated in the Dominican Republic.